Keanekaragaman Makrofauna Tanah di Kawasan Perkebunan Singkong (Manihot esculenta) Sebagai Bioindikator Kesuburan Tanah - Lufitasari, Liya; Fikri, Achmad Ali (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2023)
Fauna in the soil is a bioindicator that has a sensitive response to land management and climate. Good correlation between fauna and soil properties allows ecologists to explain land management with good productivity and health. The aim of the study was to determine the types of soil macrofauna, ecological parameters, species diversity index, and species evenness index found in cassava plantation areas. The type of research used is quantitative descriptive research. This research was conducted on 13-15 May 2023 using the Pit Fall Trap method. The results showed that there were several types of soil macrofauna found, namely Anoplolepis gracilipes, Gryllus campetis, Onthophagus trancapicus, Onthophagus trituber, Pachycondyla, Toxorhynchites, and Achatina fulica. Soil macrofauna ecological parameters are: (1) Density ranges from 0.008 ind/m² - 0.834 ind/m². (2) The frequency ranges from 0.82 – 8.34. (3) The Important Value Index (INP) of soil macrofauna in the cassava plantation area is Anoplolepis gracilipes 84.3% which is the highest. The Shannon-Wiener species diversity index (H') is in the low species diversity category with a value of 0.695547. High soil pH test results mean that the soil is classified as fertile soil. The conclusion of this study is that the diversity index of soil macrofauna found in cassava plantation areas is very influential with soil pH.